Visual Identity BW Kurir Lubuk Basung - Wivia Trirahma Melani; Fauzan Aulia (Lembaga Pengembangan Kinerja Dosen, 2023)
BW Courier was founded in 2019 as a service for picking up goods, online motorcycle taxis, delivering food, documents, and others. BW Kurir has the opportunity to make it easier for the people of Lubuk Basung Around in their daily lives. The problem finding from BW Kurir is having an inconsistent logo, color and typography as its visual identity. These problems make BW Kurir difficult to recognize by the local community, therefore this design aims to design a visual identity that is conceptualized and has a philosophy. The design uses the Glass Box method so that it is able to produce a visual identity that is consistent or easy to recognize, enhances the brand, and facilitates promotion. BW Kurir's visual identity includes logograms, logotypes, taglines, and colors that will be used in various media in the form of manual books, shopping invoices, motions, delivery bags, courier jackets, courier helmets, paper bags, x-banners, posters and feeds. Instagram.